In chasing the status as the Province of Jakarta Special Region after the movement of the capital city to East Kalimantan Province - Purba Hutapea (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2020)
The Government of of Indonesia plans to move the Capital City from Jakarta to East Kalimantan Province. The problem is what is the status of the administration of Jakarta Province after it no longer bears the status as the capital city of Indonesia. Does Jakarta Province still have the right to obtain status as a provincial region even though the government structure is not divided into municipal and regency areas, or the existing administrative area must be made an autonomous region and then legally qualify as a provincial region ?. Research Methods using qualitative descriptive methods. Based on the politics of decentralization contained in the 1945 Constitution, regarding the formation of special regions and reviews several laws which form the legal basis for granting special regions in Indonesia, or what is theoretically known as asymmetric decentralization. If the national capital is moved to East Kalimantan, the ex Jakarta Province still qualifies as a province that has special autonomy as the Province of Jakarta Special Region, because the history and role of the city of Jakarta on national government in the past cannot be forgotten. Therefore, the governance structure in the form of one level of autonomy is maintained, and the central government can surrender or delegate greater authorities for the management of economic, trade and service sectors, such as the Nusantara Bonded Zone, including the establishment of special economic zone, so that it can play a role as a locomotive of the national economy.